2001
DOI: 10.1001/archinte.161.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Linking Primary Medical Care and Substance Abuse Services

Abstract: Individuals with alcohol and drug use problems may receive health care from medical, mental health, and substance abuse providers, or a combination of all three. Systems of care are often distinct and separate, and substantial opportunities for benefit to patient, provider, and payer are missed. In this article, we outline (1) the possible benefits of linking primary care, mental health, and substance abuse services from the perspective of the major stakeholders-medical and mental health providers, addiction c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
175
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 206 publications
(188 citation statements)
references
References 55 publications
(47 reference statements)
6
175
0
Order By: Relevance
“…26 The benefi ts of connections to primary care for patients with substance use problems included improvement of overall care, early identifi cation and treatment of conditions recognized by primary care and mental health professionals, and the possibility of improved outcomes of substance abuse treatment. 27,28 Functional assessment of the patients in our study indicated a trend toward improved physical and mental health summary scores for patients in the intervention group at the 1-year follow-up, which converged with the patients' mostly favorable qualitative assessments of care management. Future work needs to replicate this fi nding and assess outcomes with extended follow-up periods.…”
Section: Discussionsupporting
confidence: 56%
“…26 The benefi ts of connections to primary care for patients with substance use problems included improvement of overall care, early identifi cation and treatment of conditions recognized by primary care and mental health professionals, and the possibility of improved outcomes of substance abuse treatment. 27,28 Functional assessment of the patients in our study indicated a trend toward improved physical and mental health summary scores for patients in the intervention group at the 1-year follow-up, which converged with the patients' mostly favorable qualitative assessments of care management. Future work needs to replicate this fi nding and assess outcomes with extended follow-up periods.…”
Section: Discussionsupporting
confidence: 56%
“…Although our findings are consistent with the literature in this area, we add to that literature in a substantial way by reporting on this prospective cohort and by considering a range of clinical characteristics assessed first hand using standardized tools, by including a range of drugs of choice, and by focusing on a common characteristic in substancedependent adults-lack of regular primary medical care. Given that people who enter detoxification often have no medical or addiction follow-up care, [53][54][55][56][57] this is an opportune moment during which people at particularly high risk can be identified and potential interventions can be developed. As the risk for death among detoxification patients overall is elevated, even among those without specific risk factors, attention should be given as to how best to address these individuals_ health needs.…”
Section: Discussionmentioning
confidence: 99%
“…One can speculate that an organizational distance exists between substance abuse treatment programs and traditional medical institutions like hospitals. However, once this organizational distance is overcome, geographic proximity between a hospital and its treatment unit might have facilitated successful linkage to services (Samet, Friedmann, & Saitz, 2001). However, affiliation with a mental health center had the expected effect on service availability: programs with such an affiliation were twice as likely to offer mental health care.…”
Section: Discussionmentioning
confidence: 99%